2014
DOI: 10.1186/s12858-014-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression, characterization and activity comparisons of wild type and mutant DUSP5 proteins

Abstract: BackgroundThe mitogen-activated protein kinases (MAPKs) pathway is critical for cellular signaling, and proteins such as phosphatases that regulate this pathway are important for normal tissue development. Based on our previous work on dual specificity phosphatase-5 (DUSP5), and its role in embryonic vascular development and disease, we hypothesized that mutations in DUSP5 will affect its function.ResultsIn this study, we tested this hypothesis by generating full-length glutathione-S-transferase-tagged DUSP5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…Indeed, we identified a clinically relevant serine to proline mutation (S147P) that is associated with vascular defects [ 2 ]. This mutation has been shown previously by our group to interfere with the dephosphorylating activity of DUSP5 protein [ 8 ], and makes the protein hypoactive. However, the direct causal role of S147P in vascular anomaly progression is yet to be established.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, we identified a clinically relevant serine to proline mutation (S147P) that is associated with vascular defects [ 2 ]. This mutation has been shown previously by our group to interfere with the dephosphorylating activity of DUSP5 protein [ 8 ], and makes the protein hypoactive. However, the direct causal role of S147P in vascular anomaly progression is yet to be established.…”
Section: Introductionmentioning
confidence: 86%
“…A molecular model based on the crystal structures of the human DUSP5 PD and ERK2, and a homology model of the DUSP5 EBD, illustrates the bivalent nature of the interaction between the two domains of DUSP5 and the ERK2 substrate (Fig. 1 ) [ 8 ]. The current study has identified small molecule inhibitors that occupy the active site pocket on the DUSP5 PD, and act as inhibitors of the phosphatase enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Of the different Dusp genes, five have been reported to prefer p38 and JNK over ERK1/2, including DUSP1, DUSP4, DUSP8, DUSP10, and DUSP16. Three cytoplasmic DUSPs: DUSP6, DUSP7, and DUSP9 were reported to be ERK1/2 specific ( Dickinson and Keyse, 2006 ), and one inducible nuclear DUSP, the DUSP5, was shown to be nuclear ERK1/2 specific ( Nayak et al, 2014 ). However, both DUSP7 and DUSP9 may also be able to inactivate p38 ( Dickinson and Keyse, 2006 ).…”
Section: Mitogen Activated Protein Kinase (Mapk) Pathwaymentioning
confidence: 99%
“…We mutated E264 to leucine (L) (E264L) and glutamine (Q) (E264Q) and R214 to glutamine (Q) (R214Q) using site-directed mutagenesis. We generated GST-tagged versions of these proteins in bacteria as described in our previous work 14 and purified them on a GST column. Upon expression of these point mutants in bacteria, we noticed three bands on the SDS-PAGE gel for E264Q and R214Q compared to four distinct bands (E264L1-E264L4, from top to bottom, respectively) in the E264L preparations (in Figure 5B, compare lanes E264L and E264Q).…”
Section: Site-directed Mutational Analysis Confirms the Importance Ofmentioning
confidence: 99%
“…Generation and Characterization of the DUSP5 Point Mutant Proteins Protein expression, GST pull-down assays, and purification protocols were similar to those reported in our previous work on GST-DUSP5 protein. 14 Modifications to the protocol included transfecting final sequenced plasmids into expression competent cells such as Shuffle cells. Shuffle cells are an Escherichia coli strain that allows for the production of proteins with disulfide bonds.…”
mentioning
confidence: 99%